2005
DOI: 10.1093/nar/gki551
|View full text |Cite
|
Sign up to set email alerts
|

An SOS-regulated operon involved in damage-inducible mutagenesis in Caulobacter crescentus

Abstract: DNA polymerases of the Y-family, such as Escherichia coli UmuC and DinB, are specialized enzymes induced by the SOS response, which bypass lesions allowing the continuation of DNA replication. umuDC orthologs are absent in Caulobacter crescentus and other bacteria, raising the question about the existence of SOS mutagenesis in these organisms. Here, we report that the C.crescentus dinB ortholog is not involved in damage-induced mutagenesis. However, an operon composed of two hypothetical genes and dnaE2, encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
149
0
35

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(193 citation statements)
references
References 50 publications
9
149
0
35
Order By: Relevance
“…The same phenotype resulted from deletion of imuA′ and was complemented by integration of a wild-type copy of imuA′. These data established the individual essentiality of ImuA′ and ImuB for induced mutagenesis and confirmed the designation of the mycobacterial ImuA′ as a distant homolog of ImuA (5,6). Msm imuA′ and imuB deletion mutants were hypersensitive to mitomycin C (MMC), a genotoxic agent known to induce the SOS response in mycobacteria (1) (Fig.…”
Section: Imua′ and Imub Are Individually Essential For Dnae2 Function Insupporting
confidence: 56%
See 2 more Smart Citations
“…The same phenotype resulted from deletion of imuA′ and was complemented by integration of a wild-type copy of imuA′. These data established the individual essentiality of ImuA′ and ImuB for induced mutagenesis and confirmed the designation of the mycobacterial ImuA′ as a distant homolog of ImuA (5,6). Msm imuA′ and imuB deletion mutants were hypersensitive to mitomycin C (MMC), a genotoxic agent known to induce the SOS response in mycobacteria (1) (Fig.…”
Section: Imua′ and Imub Are Individually Essential For Dnae2 Function Insupporting
confidence: 56%
“…S2) and strongly implies that these proteins cannot function as DNA polymerases (22). In turn, this observation suggests a model for translesion synthesis in which DnaE2 itself catalyzes lesion bypass (6).…”
Section: Imua′ and Imub Are Individually Essential For Dnae2 Function Inmentioning
confidence: 95%
See 1 more Smart Citation
“…These data confirmed that UmuDpR is a transcriptional regulator able to repress the expression of SOS genes. This transcriptional control included the genes encoding RecA and LexA, the main modulators of the SOS response, and the imuA gene, which has been involved in DNA-damage-induced mutagenesis in the alphaproteobacterium Caulobacter crescentus (Galhardo et al, 2005). Transcription of the phl gene, which encodes a photolyase-like enzyme that repairs UV-induced DNA lesions, showed no significant changes in both the lexA 2 mutant and in its umuDpR transformant (Fig.…”
Section: Umudpr Regulates Expression Of Sos Genesmentioning
confidence: 99%
“…Recently, we have demonstrated that a three-gene operon encoding a hypothetical protein (ImuA), a protein similar to members of the Y family of DNA polymerases (ImuB), and a second copy of dnaE (DnaE2) is responsible for the DNA damage-inducible mutagenesis in Caulobacter crescentus, a function performed by the UmuDC proteins in E. coli. (25). This SOS-regulated operon is widespread in Bacteria (1) and was recently shown to be part of the SOS-mediated response to the antibiotic ciprofloxacin in Pseudomonas aeruginosa (11), demonstrating the relevance of expanding the knowledge about the SOS regulatory circuit in other models.…”
Section: Na1000 Uvramentioning
confidence: 98%